Belize : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that Belize's economic growth accelerated to 11 percent in 2000, but declined to 5 percent in 2001 as a result of several hurricanes, terrorist attacks in the United States, and a shrimp-virus epidemic. Confidence was also affected by financing difficulties at the Development Finance Corporation (DFC) and the continued widening of the central government deficit from 10 percent of GDP to 12 percent in FY2001/02 (fiscal year end-March). The deficits were financed mainly through privatization receipts and external borrowing, mostly on commercial terms.